Convex pillar paintings in church interiors: context, materials and conservation problems - Sven Van Dorst (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Convex paintings which are attached to the columns of church interiors are rare and often considered a curiosity. Nevertheless, twenty-five examples where found in Europe, dating from the end of the 15th century to the beginning of the 20th century. Most of these were used as epitaph or placed above a collection box. The paintings were executed on wood, canvas or metal plate, depending on the local uses and/or period of creation. Degradation is often initiated by environmental factors like a microclimate and striking sunlight.